Sebaran Tingkat Kemasaman Tanah dan Potensial Redoks serta Kedalaman Pirit (FeS2) pada Lahan Sulfat Masam di Kecamatan Alalak - Fandi Khairany Ahmad; Muhammad Mahbub; Abdul Hadi (Acta Solum, 2024)
Acid sulfate soil has a layer of pyrite, when it is oxidized, can acidify the soil. The presence of pyrite in acid sulfate soils is very diverse and must be known. Not knowing the depth of pyrite can have fatal consequences, because layers of pyrite can be lifted to the surface due to tillage so that it oxidizes. This study aims to determine and map the distribution of pyrite depth, soil pH, and redox potential. Soil samples were determined with an exploratory descriptive method through land surveys and supported by laboratory analysis of pH, Eh and FeS2. The results showed that acidity of acid sulphate soil at all sample points was classified as very acid, Eh was classified as low reduction till oxidation. Based on the results of observations of pyrite depth, 3,492.15 ha (78.1%) was actual acid sulfate soil and 979.13 ha (21.9) was potential acid sulfate soil. So proper management is needed when turning over the soil so that the pyrite is not exposed, applying lime, organic material and regulating the water level so that the groundwater level is not below the depth of the pyrite